Naval ceremonies, customs, and traditions - Connell, Royal W. 1948- (Naval Institute Press, 2004)
First published in 1934, this book has enjoyed a reputation both as an authoritative guide to conduct in a contemporary maritime setting and a fascinating historical reference on the ways of the sea and sailor going back to the earliest days of sail. Now updated to cover all the sea services, this new edition fully reflects today's diverse force while at the same time exploring the maritime history of the United States, its flag, and the U.S. Navy's uniforms. A new chapter on naval ceremonies offers more details than ever on such events as award presentations and changes of command. A separate chapter on the popular "Dining In" ceremony explains its beginnings and evolution and tells how to plan and execute such an event. There is also greater coverage of Marine Corps and Coast Guard history and traditions. In addition to discussing the derivation of traditions and customs of the sea services, this latest update has been reorganized for ease of use by the professional seaman planning an upcoming event as well as the armchair sailor curious about the origins of naval customs and terms. It is the only up-to-date book on the subject available.